Pharmacokinetics, Immunogenicity and Safety Study for SHR-1309 Injection and Perjeta® in Healthy Chinese Male Volunteers - Cui, Yingzi; Cui, Dongyang; Ren, Xinran; Chen, Xuesong; Liu, Guangwen; Liu, Zhengzhi; Wang, Yanli; Qu, Xinyao; Zhao, Yicheng; Yang, Haimiao (Frontiers in Pharmacology, 2021)
Objectives: Pertuzumab is a monoclonal antibody for the treatment of breast cancer. The aim of this study was to compare the pharmacokinetics, immunogenicity and safety of the test preparation SHR-1309 injecta and the reference preparation Perjeta® in healthy Chinese male subjects. Methods: In this randomized, double-blind, single dose, two-way, parallel bioequivalence trial, a total of 80 qualified Chinese male subjects were selected and randomly divided into two groups. Each subject was intravenously injected with SHR-1309 or Perjeta®. Blood samples were collected at 21 different time points for pharmacokinetic analysis. In addition, immunogenicity was assessed at five different time points. The safety of the medication was monitored throughout the whole trial. Results: Cmax and AUC0-t were the primary pharmacokinetic parameters. Under a 90% confidence interval, their geometric mean ratios were 98.30 and 88.41% for SHR-1309 injection and Perjeta®, respectively. The geometric mean ratio of secondary pharmacokinetic parameters AUC0-∞ was 88.58%. These evaluation indexes are in the standard range of 80–125%, so SHR-1309 can be considered bioequivalent to Perjeta®. After 1,680 h (day 70) of administration, the two groups had 12 and 13 subjects who produced antidrug antibody (ADA), respectively. The occurrence time and proportion of ADA in SHR-1309 and Perjeta® were similar between subjects, and they had similar immunogenicity. During the entire trial period, there were 71 drug-related adverse reactions in 29 subjects who received SHR-1309 and 61 drug-related adverse reactions in 32 subjects who received Perjeta®. The incidence of adverse reactions between the two drugs was similar. Conclusion: The pharmacokinetic parameters, immunogenicity and safety of the biosimilar SHR-1309 injection produced by Shanghai Hengrui Pharmaceutical Co. Ltd. were similar to the original drug Perjeta® produced by Roche Pharma AG. The two drugs met the bioequivalence evaluation criteria. Therefore, SHR-1309 is bioequivalent to Perjeta®. Clinical trial registration: CTR20200,738.